Scripted attachment representations and adaptive functioning during early childhood. Issue 3 (4th May 2019) - Nichols, Olivia; Vaughn, Brian E.; Lu, Ting; Krzysik, Lisa; El-Sheikh, Mona
ABSTRACT: Attachment theorists have characterized children's internal working models, forged from early attachment relationship histories, as the link between earlier and later manifestations of competence. In this study, working models of attachment were measured as access to and use of the secure base script (SBS) to organize children's attachment relevant narratives (N = 139). Study goals were to assess relations between SBS use and a range of adaptive functioning domains including peer social competence, teacher/child relationships, effortful control, executive function, and verbal intelligence. Simultaneous path analyses using structural equations indicated that SBS use was significantly associated with each of these outcome domains. Findings were reproduced when effects of verbal intelligence, sex and age were controlled, except for effortful control. Results suggest that children's internalized attachment representations are intertwined with adaptive functioning during early childhood.